Trend and effect of inbreeding on survivability and performance traits in closed herd of Karan Swiss and Karan Fries cattle - SINGH, M K; GURNANI, M (The Indian Journal of Animal Sciences, 2014)
Data on 1021 Karan Swiss females sired by 49 pulls and 1422 Karan Fries females sired by 56 bulls during 1980 to 1992 were used to study the trend of inbreeding over the years and generations and the effect of inbreeding on survivability, growth, reproduction and production traits. The average annual increase in inbred and their inbreeding coefficient were 0.79 and 0.22% in Karan Swiss and 1.10 and 0.37% in Karan Fries herds, respectively. The inbreds, their inbreeding coefficient and inbreeding coefficient of all females were 36.2, 3.3 and 2.0% in Karan Swiss and 21.0, 6.6 and 1.4% ub Karan Fries respectively. Fluctuating trends in both heards were observed over the years and generations for number of inbred animals and for their average inbreeding coefficient. The effect of inbreeding was significant on body weight at birth 3,6,12 months age, WFS, WFC,FSP, FCI and MY/FCI in Kara Fries and survivability up to first calving, FDP and EBE in karan Swiss cattle. Declined performance and survivability of varying magnitude were recorded among inbreds. To control the rate of inbreeding unrelated or distabtly animals or elite bulls from out side may be used.